Local Government Policy Initiatives in Probolinggo Regency for the Prevention and Control of HIV/AIDS Based on Probolinggo Regent Regulation No. 25 of 2016 on the Prevention and Control of HIV and AIDS - Daroini, Rofilah Khasanatun; Hitaminah, Khusnul; Rohim, Abdur (Indonesian Journal of Law and Economics Review, 2026)
General Background: HIV/AIDS remains a multidimensional public health issue affecting legal, social, economic, and healthcare systems at global, national, and regional levels. Specific Background: In response to increasing HIV/AIDS concerns, the Probolinggo Regency Government enacted Regent Regulation Number 25 of 2016 as a legal framework for HIV/AIDS prevention and control through preventive, curative, and rehabilitative programs. Knowledge Gap: Previous studies have largely emphasized medical and public health perspectives, while limited empirical legal research has examined the implementation of regional HIV/AIDS regulations and the practical challenges faced by local governments. Aims: This study aims to analyze the implementation of HIV/AIDS prevention and control policies in Probolinggo Regency and identify obstacles encountered in applying Regent Regulation Number 25 of 2016. Results: Using an empirical legal method with a socio-legal approach, the study found that the local government implemented public education programs, Voluntary Counseling and Testing (VCT) services, Antiretroviral Therapy (ART), psychosocial assistance, and cross-sector coordination involving the Health Office and the AIDS Prevention Commission. However, policy implementation remains constrained by limited financial resources, inadequate healthcare personnel, weak inter-agency coordination, uneven healthcare access, insufficient monitoring systems, and persistent social stigma and discrimination against people living with HIV/AIDS. Novelty: This research integrates normative and empirical legal analysis while specifically examining the implementation of a regent regulation within the local context of Probolinggo Regency. Implications: The findings highlight the importance of strengthening institutional coordination, improving resource allocation, expanding healthcare accessibility, and increasing community awareness to support sustainable HIV/AIDS governance at the regional level. Highlights: Preventive, treatment, and rehabilitation programs were implemented through VCT, ART, and public outreach initiatives. Resource shortages, institutional coordination gaps, and healthcare accessibility barriers limited program execution. Social stigma and discrimination continued to reduce community participation in testing and treatment services. Keywords: Local Policy, HIV/AIDS, Local Government